PERANCANGAN PENINGKATAN DAYA SAING UKM BANDENG DI KABUPATEN SIDOARJO DENGAN METODE QUALITY FUNCTION DEPLOYMENT(QFD) - Rina Sri Wulandari; Rizki Amalia Putri (Journal of Research and Technology, 2018)
Sidoarjo has become one of the districts with the largest number of SMEs and milkfish processing SMEs being one of the superior in Sidoarjo District. However, the increasing number of milkfish processing industries even from outside Sidoarjo District has caused this industry has to be able to compete with various similar businesses from various regions. Therefore, a strategy is needed to improve SMEs competitiveness of processed milkfish. According to these problems, the design of increasing the competitiveness was carried out with the method of Quality Function Deployment (QFD). The QFD method was used because this method could be used to plan and develop products in a structured manner and allowed the development team to clearly define customer needs and expectations, and evaluate the ability of a product or service systematically to meet those needs and expectations. Customer needs and expectations based on the House of Quality matrix consisted of 4 indicators including products, prices, packaging, and marketing. While the criteria used were 14 criterias. Development priorities based on House of Quality were marketing, packaging design, quality of additional materials, quality of raw materials, content of additional materials, production equipment, and the use of packaging materials. Keywords: SMEs, Quality Function Deployment, House of Quality.